Improved damage sensing with random/aligned carbon nanofiber in bulk epoxy and adhesive joints. Issue 9 (23rd July 2022) - Chanda, Amit; Sinha, Sujeet K.; Datla, Naresh V.
Abstract: In situ health monitoring of polymeric materials and adhesive joints can be done by adding conductive carbon nanofillers that enable inherent piezoresistive sensing capability in nonconductive polymers. In this study, carbon nanofiber (CNF) was added to epoxy in bulk and adhesive form to investigate their potential applications as strain and crack detection sensors, respectively. Tensile specimens of CNF/epoxy nanocomposites with different filler concentrations were tested to study their strain sensing capability. The nanocomposites were further used as adhesive for sensing crack propagation in adhesive joints. CNFs alignment was carried out inside the adhesive by AC electric field to study the alignment effect on crack detection capability and fracture toughness of joints. Tensile specimens showed excellent strain sensing capability at CNF concentrations of 0.4, 0.8, and 1.2 wt%. However, the gauge factor was found to be highest at 0.4 wt% and decreasing further with increasing CNF content. The CNF addition was found to enhance the crack detection capability as well as the fracture toughness in adhesive joints. Further improvements in the crack detection capability and fracture toughness were observed in the case of aligned nanocomposite joints. However, the effect of alignment was observed to be more profound at lower CNF content. Abstract :